Availability, Cost, and Popularity of African Leafy Vegetables in Accra Markets, Ghana - Asase, A.; Kumordzie, S. (Economic Botany, 2019)
Consumption of African leafy vegetables can have a positive effect on nutrition, health, and economic well-being of both rural and urban populations. In this study, we undertook a detailed evaluation of African leafy vegetables in selected Accra markets in southern Ghana. Data were collected from 50 sellers from four markets within Accra and its environs using standard ethnobotanical methods. A total of six species of African leafy vegetables belonging to five plant families were identified. Average cost of the vegetables was about USD 0.25 per bundle (weight of bundles ranges between 0.2 and 0.6 kilograms (kg)), and prices were influenced by plant species and market location. Popularity of the leafy vegetables was high as reported by 88% of the respondents. Our findings showed that only a few of the documented African leafy vegetables were available in the markets, although popularity of these vegetables was high.